Technological aspects of processing steel products in powder mixtures containing hot‑dip galvanizing waste - V. G. Dashkevich; P. S. Myshkevich; N. M. Barankevich (Литьë и металлургия)
The paper considers the technological features of thermodiffusion galvanizing of fasteners in a powder mixture containing the main waste of hot galvanizing it is gartzink. The advantages of preliminary fluxing over thermal diffusion zinc plating are noted. The microstructure of the obtained diffusion layers on steel 40Х was studied, the features of the saturation kinetics and the quality of the resulting layers were noted.